Ethnobotani Study on Mangrove Forests in Padang City and Pariaman City - Irma - Leilani; Rizki Rizki; Tuti M Sari; Dian M. Sari (UNIVERSITAS NEGERI PADANG, 2017)
There are many benefit especially for the society who live around mangrove area. The purpose of this study is to find out the species of mangrove that used by the society in Teluk Buo Padang and in Mangguang, Pariaman. This research was conducted on Mei 2012 till June 2013. This study used survey method with direct observation to the field. interviews conducted to determine the utilization of mangrove species for the surrounding community. There were 43 people in Pariaman and 33 people in Padang have been selected as the respondent. The interview aims to find out the species of mangroves that are used as medicinal plants, for foods or other benefits and how to used it. In Pariaman we found 19 species, 10 species are medicinal plants, 3 can be eaten and 18 species are used for other things. In Padang we found 17 species, 11 of them are medicinal plants, 3 can be eaten, 15 species are used for other things. Some species have many benefits by people around the mangrove forest Key words: Benefit, mangrove, Pariaman, Padang